Modulation of auroral electrojet currents using dual modulated HF beams with ELF phase offset, a potential D‐region ionospheric diagnostic. Issue 5 (3rd May 2013) - Gołkowski, M.; Cohen, M. B.; Moore, R. C.
Abstract : [1] Experiments at the ionospheric heating facility of the High Frequency Active Auroral Research Program (HAARP) are performed employing dual HF beams amplitude modulated at ELF/VLF with a phase offset between the two modulation waveforms. The amplitude of the observed ELF/VLF waves is strongly dependent on the imposed ELF/VLF phase offset, the modulation waveform, and the orientation of the HF beams. Data from two ground stations are interpreted using simulations of modulated heating power envelopes as well as a comprehensive model of ionospheric ELF/VLF generation. It is found that two colocated vertical beams HF beams excite a single ionospheric ELF/VLF source, but independent ELF/VLF sources can be induced in the ionospheric region above the heater if the HF beams are offset from zenith to intersect at their 3 dB points. Furthermore, the use of two vertical HF beams with ELF phase offset is found to be a potential diagnostic method for the ionospheric D region. Key Points: It is not feasible to create a vertical ELF phased array Dual beam phasing offers a new way to diagnose D-region in real time. Modulated HF beams separated at 3dB points excite independent ELF sources